Antibiotic Resistance and Virulence of Extraintestinal Pathogenic Escherichia coli (ExPEC) Vary According to Molecular Types - Duan, Yitao; Gao, Huihui; Zheng, Liyang; Liu, Shuangqing; Cao, Yang; Zhu, Siyuan; Wu, Zhenzhe; Ren, Hongqiang; Mao, Daqing; Luo, Yi (Frontiers in Microbiology, 2020)
Extraintestinal pathogenic Escherichia coli (ExPEC) can cause many human extraintestinal infections. Resistance and virulence of ExPEC are inextricably linked to its phylogenetic background. However, studies on type-specific distribution of resistance and virulence and the connection between resistance/virulence and molecular typing are lacking. Here, 411 ExPEC strains were collected and characterized using antimicrobial susceptibility testing and molecular typing. Among these, 74 representative strains were selected for whole genome sequencing and the Galleria mellonella killing assay. CH40-30-ST131, CH37-27-ST405, CH40-41-ST131, and CH13-5-ST12 isolates had high resistance rates to all antimicrobials tested. BlaCTX-M played a significant role in the β-lactam resistance of ExPEC isolates. CH14-64-ST1193, CH40-30-ST131, and CH35-27-ST69 isolates were highly virulent in the G. mellonella model. VFs involved in adherence (papB, papI, papX, and fimA), autotransporter (sat), invasion (aslA, kpsD), iron uptake (except for entD), or toxin (senB) might be responsible for pathogenicity in vivo. Specific ARGs or VFs were prevalent in specific types of strains, including papB, papI, fimA, sat, kpsD, senB, and aerobactin genes in CH14-64-ST1193 isolates; blaCTX-M-15, aac(6')-Ib-cr, papB, papI, sat, iucA, iucB, iucC, chuT, chuX, and shuU in CH40-30-ST131 isolates; tetB in CH35-27-ST69 and CH13-5-ST12 isolates. Type distribution also differed by VF score. CH37-27-ST405 and CH26-5-ST38 isolates carried more ARGs and VFs indicating that they had a high resistance and virulence potential. This study demonstrates the type-specific distribution of resistance and virulence thus providing a basis for further research, prevention and treatment of ExPEC infections.